Polystyrene Microplastics and Cadmium Drive the Gut-Liver Axis Through the TLR4/MyD88/NF-κB Signaling Pathway to Cause Toxic Effects on Broilers - Ruiwen Fan; Wenqi Tian; Chen Qin; Peng Li; Yuhang Sun; Miao Long; Shuhua Yang (Toxics)
Nowadays, the risk of oral intake of microplastics (MPs) and cadmium (Cd) by poultry is high. In some industrially polluted areas, the chicken feed samples contain 9.60 × 102 ± 1.09 × 102 MPs per kilogram (mean ± std) in wet weight, and the Cd content in chicken feed has been detected to reach up to 5.61 mg/kg. But scholars still focus more on the toxic effects of MPs and Cd on the liver and intestines of aquatic animals. There are few studies that use poultry as research animals and consider these two organs as an integrated system to investigate the toxicity of MPs and Cd on the gut-liver axis and the mechanisms of inflammation. Therefore, in this research, broilers were used as experimental subjects, and experimental models were established by single or combined exposure of MPs (100 mg/L) and Cd (140 mg/kg) to explore the effects of MPs and Cd on the intestinal mucosae and liver of broilers, as well as the mechanisms behind these toxic effects. In this study, the degree of adverse effects (decreased expression of tight junction proteins, changes in intestinal morphology, abundance and diversity of intestinal flora, liver inflammation) caused by the single exposure group was higher than that of the combined exposure group. The results showed that MPs and Cd induced intestinal damage and liver inflammation in broilers by interfering with the TLR4/MyD88/NF-κB pathway and intestinal flora homeostasis. The toxicity of combined exposure was lower than that of single exposure.